KEKUATAN PEMBUKTIAN ALAT BUKTI REKAMAN SUARA DALAM PERKARA TINDAK PIDANA KORUPSI (STUDI PUTUSAN NOMOR 15/PIDANA KHUSUS-TINDAK PIDANA KORUPSI/2020/PENGADILAN NEGERI SURABAYA): The Power of Proof of Voice Recording Evidence in Crime of Corruption ( Study of Decision Number 15/Special Criminal –Crime of Corruption/2020/Surabaya State Court) - Hadiyanto, Narissa Rafaputri; Setiyono (AMICUS CURIAE, 2024)
Corruption is an ongoing issue in Indonesia, with hundreds of cases occurring every year. The Corruption Eradication Commission (KPK) has special authority to conduct wiretapping as part of the investigation efforts into corruption cases. One of the frequently used pieces of evidence in wiretapping is voice recordings. In this research, a normative legal approach with a descriptive-analytical method is employed. The research aims to understand and analyze the evidential strength of voice recordings in  cases of corruption. Data is gathered through a literature review, utilizing primary sources like the 1945 Constitution of the Republic of Indonesia, the Criminal Procedure Code (KUHAP), and the Law on the Eradication of Criminal Acts of Corruption, as well as secondary sources such as legal books, legal journals, papers, and relevant articles. Qualitative analysis is the chosen data analysis method. The research findings affirm that the KPK has legitimate authority to conduct wiretapping and use voice recordings as evidence in the prosecution of corruption cases. Voice recordings are recognized as valid evidence with strong probative value, supported by decisions from the Constitutional Court and the expansion of evidentiary provisions in the KUHAP. The research's conclusion reinforces that the KPK can lawfully conduct wiretapping and employ voice recordings as evidence in accordance with applicable laws, playing a crucial role in the fight against corruption in Indonesia. Keywords: Corruption; Criminal Code; Wiretapping; KPK; Voice Recording